THE MEDIATING ROLE OF EMPLOYEE ENGAGEMENT IN THE RELATIONSHIP BETWEEN SPIRITUAL LEADERSHIP, WORKPLACE SPIRITUALITY, AND EMPLOYEE PERFORMANCE - Ahmad Sadjid Laeli (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Background:Employee performance has been widely viewed as an important issue in human resource management. In Islamic microfinance institutions, performance is not only linked with financial targets but also with service quality, ethical responsibility, and the ability to maintain trust among members. For this reason, spiritual values in leadership and the workplace may have a meaningful role. Still, the way spiritual leadership and workplace spirituality are translated into employee performance through employee engagement has not been fully explained, especially in the context of BMT. Objective:This study was designed to examine the mediating role of employee engagement in the relationship between spiritual leadership, workplace spirituality, and employee performance at BMT Beringharjo. Methods:A quantitative approach was used in this study. Data were obtained through a questionnaire distributed to employees of BMT Beringharjo. A total of 200 responses were processed. Each variable was measured using a five-point Likert scale. Spiritual leadership was reflected through vision, hope or faith, and altruistic love. Workplace spirituality was measured through meaningful work, sense of community, and alignment with organizational values. Employee engagement was assessed through vigor, dedication, and absorption, while employee performance was measured through work quality, quantity, punctuality, initiative, and work effectiveness. The data were analyzed by using Structural Equation Modeling with a mediation testing procedure. Results:The findings showed that workplace spirituality had a significant effect on employee engagement. Employee engagement was also found to have a significant effect on employee performance. In addition, workplace spirituality was shown to influence employee performance, both directly and through employee engagement. However, spiritual leadership was not found to have a significant direct effect on employee engagement and employee performance. The mediating effect of employee engagement was supported only in the relationship between workplace spirituality and employee performance. Conclusion:The study indicates that employee engagement plays an important role in linking workplace spirituality with employee performance. In the context of BMT Beringharjo, the spiritual atmosphere of the workplace seems to be more strongly felt by employees than leadership influence alone. This suggests that value-based work environments may become a practical path for strengthening employee engagement and improving performance. Spiritual leadership remains relevant, yet its influence may depend on how far spiritual values have already been embedded in daily organizational practices.